2012
DOI: 10.1016/j.jcin.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Nobori Stent Shows Less Vascular Inflammation and Early Recovery of Endothelial Function Compared With Cypher Stent

Abstract: Our data show significantly lower inflammatory response in the stented segments, and rapid recovery of endothelial function of peristent segments in the Nobori group compared with Cypher DES group at 1 month in porcine coronary artery model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…38 Similarly, Pendyala et al revealed a significantly lowered inflammatory response in the stented segments and rapid recovery of endothelial function in persistent segments in the BES group compared with the Cypher group. 39 We speculate that a lower inflammatory response and rapid recovery of endothelial function after BES implantation might protect against atherogenic change. Larger and longer follow-up studies are warranted to validate our hypothesis.…”
Section: Atherosclerotic Changes In the Neointima After Bes Implantationmentioning
confidence: 87%
“…38 Similarly, Pendyala et al revealed a significantly lowered inflammatory response in the stented segments and rapid recovery of endothelial function in persistent segments in the BES group compared with the Cypher group. 39 We speculate that a lower inflammatory response and rapid recovery of endothelial function after BES implantation might protect against atherogenic change. Larger and longer follow-up studies are warranted to validate our hypothesis.…”
Section: Atherosclerotic Changes In the Neointima After Bes Implantationmentioning
confidence: 87%
“…We had already reported that BES revealed significantly lower inflammatory response as compared with SES [16]. Hagiwara reported that inflammatory score and injury score in BES were comparable to even bare metal stent at 30 days in histological analysis [17].…”
Section: Accepted Manuscriptmentioning
confidence: 89%
“…The polymer used in DES facilitates the controlled elution of antiproliferative drugs over a period of time. However, once drug elution has been completed, durable polymers have been implicated as potential triggers for late and very late stent thrombosis [19,20]. Biodegradable polymers, as opposed to durable polymers, can be completely metabolized, potentially reducing the risk of late complications such as stent uncovering, malapposition, and endothelial dysfunction [19].…”
Section: Discussionmentioning
confidence: 99%